GCT-45. YOLK SAC TUMOR IN THE CEREBELLAR VERMIS - A CASE REPORT. (4th December 2020) - Otake, Saori; Matsutani, Tomoo; Watanabe, Yousuke; Numata, Osamu; Ando, Ryo; Ochiai, Hidemasa; Junichiro, Ikeda; Iwadate, Yasuo
Abstract: Yolk sac tumor (YST) is a non-germinomatous malignant germ cell tumor in a young child. It usually arises along a midline axis, mostly pineal region or suprasellar compartment, and it is exceedingly rare to locate in a cerebellar vermis. In the present report, we describe a case of a pure YST located in the cerebellar vermis and review the previous literature. A three-year-old boy visited a local clinic for gait disturbance and frequent vomiting. Gadolinium-enhanced magnetic resonance imaging (MRI) showed a homogeneously-enhanced mass with a cystic component in his cerebellar vermis, and it resulted in hydrocephalus. By its location and his age, our pre-operative diagnosis was a medulloblastoma, and we performed a total resection of the tumor with ventricular drainage. Unexpectedly, the histological investigation revealed it to be a YST. We confirmed that the serum levels of α-fetoprotein (AFP) had elevated at 3176.4 ng/ml in his preserved sample, obtained before the surgery, and it was consistent with the pathological diagnosis. He is receiving chemotherapy consisting of ifosfamide, cisplatin, and etoposide, followed by radiation therapy. In this case, pre-operative MRI revealed that the tumor did not grow into the IVth ventricle in spite of midline location, which was not typical for medulloblastoma. Of note, serum AFP levels had increased, and they might contribute to a precise pre-operative diagnosis and be able to propose an alternative treatment plan, such as neoadjuvant chemotherapy to reduce surgical risk. As a conclusion, a YST should be considered even if it locates in a cerebellar vermis.